South Asia Regional Office (SAR) - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Achieving food and nutrition security is a complex challenge. This is especially true in South Asia, where 40 percent of the world’s poor—who survive on less than US$1.25 a day—live and 21 percent of the population is undernourished. Yet countries in South Asia have seen marked improvements in socioeconomic development in recent years. South Asia encompasses only 3 percent of the world’s land, but is home to about a quarter of the world’s population (1.6 billion people). While agriculture is a critical component of food and nutrition security, it is interlinked with water, energy, infrastructure, and policy challenges. Apart from this, natural resources are under additional pressure due to population growth, income growth, urbanization, changing consumer preferences, and climate change. Against this backdrop, the IFPRI South Asia Regional Office (SAR) in New Delhi engages in evidence-based policy research and capacity-building activities related to food and nutrition security in the region. The research focuses on agricultural diversification, climate change, markets and trade, nutrition and health, science and technology, and governance, contributing directly to the strategic research areas established by IFPRI’s 2018–2020 Strategy.